Where is the Clinical Breakthrough of Heme Oxygenase-1 / Carbon Monoxide Therapeutics? - Hopper, Christopher P.; Meinel, Lorenz; Steiger, Christoph; Otterbein, Leo E. (Current Pharmaceutical Design, 2018)
Heme oxygenase (HO), the rate-limiting step in the degradation of heme to biliverdin, ferrous ion, and carbon monoxide (CO), is an ancestral protective enzyme conserved across phylogenetic domains. While HO was first described in the late 1960s and progressively characterized in the following decades, there has been a surge of innovation over the past twenty years in efforts to leverage the cytoprotective power of HO in a clinical setting. Despite the plethora of preclinical data indicating extraordinary therapeutic potential, HO has remained elusive from the physician's toolbox. The leading candidate in development, CO, has long been misconstrued as a useless toxic gas. Scientists have crafted an array of CO delivery molecules and devices to harness HO, however, each endeavor was met with limitations preventing translation into clinical practice. In this discussion, we summarize the HO / CO field with a clinical and commercial development perspective. More specifically, given the enormous global efforts and capital investment into the field, we ask: where is the breakthrough therapy?
Keywords: anesthetics